Screening and optimization of solid-state fermentation conditions of high cellulase-producing strain and its enzymatic property - WANG Caiyi, XIA Jingwen, PANG Bingyu, QIN Liyuan, CHENG Zhong, ZHANG Ting (Zhongguo niangzao)
In this study, the high cellulase-producing strain was screened from 12 fungi preserved in the laboratory, and identified by morphological observation and molecular biology techniques. Using cellulase activity as the evaluation index, the solid-state fermentation conditions of the screened strain were optimized by single factor tests and orthogonal tests, and the cellulase activity was compared with that of the reported high cellulase-producing strains. Finally, the enzymatic properties of the crude cellulase were preliminarily investigated. The results showed that a high cellulase-producing strain of Trichoderma asperellum BW-6 was screened and identified, with the filter paperase (FPase) and carboxymethyl cellulase (CMCase) activities reached 1.99 U/g and 7.02 U/g, respectively, and the optimal solid-state fermentation conditions were as follows: wheat bran+ bagasse+rice straw (2.0 g+1.5 g+1.5 g) as solid-state fermentation substrate, 0.5% peptone in basic salt solution medium as nitrogen source, fermentation broth addition 6 ml, and static culture at 26 ℃ for 5 d. Under these conditions, the filter paperase and the carboxymethyl cellulase activities reached 2.81 U/g and 10.15 U/g, respectively, which were 1.41 and 1.46 times that of before optimization, and were extremely higher than that of Penicillium oxalicum EU2101 and EU2106 under the same conditions (P<0.01), indicating that the strain BW-6 had the potential for industrial application. In addition, the optimal reaction temperature and pH of the cellulase produced by strain BW-6 were 50 ℃ and 4.0, respectively, and it was stable at 45 ℃ and pH 5.5-6.0.